Anti-inflammatory and antinociceptive effects of kaempferide from the Brazilian green propolis (Research, Society and Development, 2020)
The Brazilian green propolis is produced by Apis mellifera from Baccharis dracunculifolia. Kaempferide, which was isolated from green propolis and B. dracunculifolia is an O-methylated flavonol bearing gastroprotective, anti-allergic and anti-hypertensive activities. Thus, the aim of this study was to evaluate the anti-inflammatory and antinociceptive potentials of kaempferide, as well as its possible toxicological effect on kidney and liver. For that, nociception was assessed by thermal (hargreaves apparatus) and mechanical (Dynamic Plantar Aesthesiometer) sensitivities; anti-inflammatory potential was assessed by carrageenan induced edema; and the toxicological profile was assessed by blood biochemical assessment. Kaempferide significantly reduced mechanical nociception and displayed anti-inflammatory effect, which was evidenced by the reduction of the volume of the paw edema, as well as by the reduction of infiltrates, cellularity and area of the injured tissue. On the other hand, it was inactive in the thermal nociception protocol either with or without an inflammatory process, as well as it was inactive in the mechanical nociception protocol after an inflammatory process. In addition, central nervous system depression, liver and kidney toxicities were not observed.